Design and Validation of an Emotional Education Program for Students With Attention Deficit Disorder and Hyperactivity - Cabello-Sanz, Sandra (2025)
Objective. The aim of this work was the design and validation of a Program to improve the emotional competences of students with Attention Deficit Hyperactivity Disorder (ADHD). Method. An epistemological and normative review of the subject, a systematic review of the main programs that have been developed in this respect, as well as validation by a group of experts and a pilot test with a control and experimental group were carried out. Results. The Program has high internal consistency, derived from the high degree of adequacy of the variables and the concordance between the experts. Analysis of inter-expert agreement using Kendall's coefficient (W = .65) indicated a moderate level of agreement, while the internal consistency of the form, as measured by Cronbach's alpha (α = .77), reflected acceptable reliability. The experimental group obtained higher emotional competence scores than the control group. Conclusions. This Program can be useful not only for working on emotional competences with primary school students, but it also provides the robustness of having undergone an assessment to accurately measure these competences.